Validity and reliability: instruments of teacher competency in the context of small schools in Peninsular Malaysia - Mohd Razali, Mohd Norlizam; A. Hamid, Aida Hanim; Alias, Bity Salwana; Mansor, Azlin Norhaini (Journal of Education and Learning (EduLearn), 2025)
A teacher competency instrument was developed to determine the level of teacher competency in small schools in Peninsular Malaysia. This study was conducted in Perak and Negeri Sembilan to determine the instrument's reliability and validity. Exploratory factor analysis (EFA) and item reliability analysis were used to determine the questionnaire's reliability and validity. Next, the average congruence percentage (ACP) is used to determine the reliability test between expert assessors. Experts approved the validity and reliability of the instrument before the EFA test was conducted. All four constructs have high-reliability index values between 0.82–0.92. Next, the EFA analysis shows four dimensions in the teacher competency instrument with factor loadings (FL) ranging from 0.60–0.88. The findings also show that the variance explained in the data is 58.46% with an Eigenvalue greater than 1. This result indicates that all items were received with high approval. In addition, a very high-reliability coefficient value, α=0.82. The results prove that this teacher competency instrument has high validity and reliability and can measure the level of teacher competency implementation practices in small schools in Peninsular Malaysia.